The Role of Human Resource Management in Adoption o f Quality Management Systems i n Kenya’s Iso Certified State Corporations - Weru, Jane Muthoni; Gachunga, Hazel; Odhiambo, Romano (My University, 2017)
Purpose: The general objective of this study was to determine the role of Human Resource Management in the adoption of quality management systems in Kenya’s ISO certified state corporations. Materials and methods: The proposed research consisted of a descriptive survey. The population comprised a total of fifty nine state corporations that were ISO certified on 9001:2008 series by the Kenya Bureau of Statistics. The study applied a stratified random sampling technique to select a sample size of twenty one state corporations from the fifty nine which was a third of the target population. Purposive sampling technique was further applied to select a total of four respondents in each of the twenty one selected state corporations. Results: Findings indicate that there is poor leadership in Kenya’s state corporations that Kenya’s state corporation lacks best hiring practices as a result competence is not emphasized in the organizations. Additional results provided showed that State owned corporations in Kenya have not adopted any performance management systems and the few that have adopted have a performance management system that does not meet the required standards. Further findings shows that there is a great interaction among employees of the same gender and to a small extend amongst other employees of the opposite gender which enables them to achieve organizational objectives. Recommendations: Inferential statistics from the analysis recommends that employees’ interaction and networking is an important ingredient that would fasten the adoption of quality management systems in Kenya’s state owned corporations. Leadership capabilities, competence management performance management and human resource information systems are very important in ensuring adoption of quality management systems.
Keywords: Human resource management role; Quality management systems; ISO certified state corporations